Tackling Challenging Data Integrity Topics in 2020: Update on Good Clinical Practice Perspectives from the US FDA and MHRA UK. Issue 1 (30th August 2021) - Khin, Ni A.; Grandinetti, Cheryl; Dixey, Hayley; Yu, Bei; Skeete, Rachel; Ayalew, Kassa; Budwal‐Jagait, Mandy; Cho, Seongeun‐Julia; Dasgupta, Arindam; Fisher, Andrew; Kleppinger, Cynthia; Kronstein, Phillip D.; et al.
Abstract : With the globalization of clinical trials, regulators have increased collaboration to evaluate the adequacy of clinical trial conduct and to optimize regulatory oversight. The 2020 joint Good Clinical Practice (GCP) symposium of the US Food and Drug Administration and the UK Medicines and Healthcare products Regulatory Agency provided the agencies' perspectives on the challenges in ensuring data quality in novel clinical trial designs and the importance of the management and documentation of protocol deviations, sponsor oversight of clinical trials, and use of electronic source data, including electronic health records. This paper summarizes considerations of both agencies on these topics, along with case examples. This paper touches upon considerations when using real‐world data to support regulatory decisions. It also discusses the impact of the coronavirus disease 2019 (COVID‐19) pandemic on clinical trial conduct and underscores the importance of well‐designed, resilient, and adaptable systems for GCP compliance and data integrity.